An international survey on clinicians' perspectives on the diagnosis and management of chronic intestinal pseudo‐obstruction and enteric dysmotility. Issue 12 (22nd July 2020) - Vasant, Dipesh H.; Pironi, Loris; Barbara, Giovanni; Bozzetti, Federico; Cuerda, Cristina; Joly, Francisca; Mundi, Manpreet; Paine, Peter; Staun, Michael; Szczepanek, Kinga; Van Gossum, André; Wanten, Geert; et al.
Abstract: Background: Chronic intestinal pseudo‐obstruction (CIPO) and enteric dysmotility (ED) are small intestinal motility disorders defined by radiological and manometric criteria. In the absence of consensus guidelines, we surveyed opinions on the diagnosis and management of CIPO and ED among experts from different countries. Methods: A survey questionnaire was circulated electronically to members of the European society for Clinical Nutrition and Metabolism, European Society of Neurogastroenterology and Motility, and United European Gastroenterology. Only responses from participants completing all required components were included. Key Results: Of 154 participants, 93% agreed that CIPO and ED should be classified separately. Overall, 73% reported an increasing incidence of CIPO and ED, with hypermobile Ehlers‐Danlos Syndrome the group with the largest increase in referrals (37%), particularly in the UK ( P  < .0001). The majority (95%) find diagnosing CIPO and ED difficult. Notably, antroduodenal manometry, a test mandated to diagnose ED, is infrequently used (only 21% respondents use in >50% cases) and full thickness biopsies were reported to seldom influence medical treatment, nutritional management, and prognosis. Respondents reported that very few treatments are useful for most patients, with bacterial overgrowth treatment, prucalopride, and psychological therapies felt to be the most useful. While only 23% of clinicians felt that parenteral nutrition (PN) improves gastrointestinal symptoms in >50% of cases, 68% reported PN dependency at 5 years in the majority of cases. Conclusions and Inferences: These data highlight the difficulties with diagnosing and managing CIPO and ED and underscore the urgent need for international, multidisciplinary, clinical practice guidelines. Abstract : Variability in expert clinicians practices on use of motility investigations in diagnosing CIPO and ED.